EMOTIONAL COACHING UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL ANAK DI LINGKUNGAN TPA BANTARGEBANG - Sri Mulyani Nasution; Nursafitri; Mukti Utama (Politeknik Negeri Sriwijaya, 2023)
This community service aims to (1) Develop the Emotional Intelligence of Children in the Bantargebang TPA environment, (2) Provide Emotional Coaching to parents in the Bantargebang TPA environment, (3) Provide education about the importance of emotional intelligence for children's success in the future. Primary data was obtained through a survey of respondents taken from the parents of children in the Bantargebang TPA environment. Secondary data were obtained from interviews with important figures in the Bantargebang TPA environment along with literature studies from various sources of information. The survey analysis used quantitative descriptive analysis. The results of the study indicate a lack of public knowledge and socialization carried out by the local government regarding how to raise children to increase emotional intelligence. Following up on the results of the study, the researchers conducted an intervention in the form of Emotional Coaching to equip parents with independency in how to improve children's emotional intelligence.